2010
DOI: 10.1093/jaoac/93.1.190
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Gliadin and Glutenin Fractions in Four Commercial Gluten Assays

Abstract: Gluten sensitivity affects nearly 1 of the population in the United States and Europe. To help these consumers avoid the health issues that result from gluten consumption, the U.S. Food and Drug Administration is attempting to establish a definition and testing protocol for gluten-free foods. Establishing this protocol depends on accurate tests that can detect and quantitate gluten. There are multiple immunoassays available for the quantitation of gluten, and most are based on one of two antibodies. These anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 2 publications
2
15
1
1
Order By: Relevance
“…We believe this is valuable information to aid the understanding of mAb specificities and the selection of a set of appropriate gluten markers. The results obtained also suggest, in accordance with previous research (Allred and Ritter 2010;van Eckert et al 2010;Sharma 2012), that assay antibodies could interact with glutenin proteins, mainly HMW-GS. That certain antibodies also react with the glutelin fraction has already been shown by Rallabhandi et al (2015) and Lexhaller et al (2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We believe this is valuable information to aid the understanding of mAb specificities and the selection of a set of appropriate gluten markers. The results obtained also suggest, in accordance with previous research (Allred and Ritter 2010;van Eckert et al 2010;Sharma 2012), that assay antibodies could interact with glutenin proteins, mainly HMW-GS. That certain antibodies also react with the glutelin fraction has already been shown by Rallabhandi et al (2015) and Lexhaller et al (2016).…”
Section: Discussionsupporting
confidence: 91%
“…Sharma (2012) reported that the 401.21 mAb could be reacting to LMW-GS because these proteins could be derived from modified components of the w-gliadin fraction. However, our experiments and previous reports strongly suggest it is more likely that the 401.21 mAb reacts to HMW-GS fractions (Allred and Ritter 2010;van Eckert et al 2010) as well as the w-gliadin proteins (Skerritt and Hill 1990) but not LMW-GS.…”
Section: Discussionsupporting
confidence: 51%
“…However, ELISA is very expensive, and the reproducibility of the results varies depending on the ELISA test kit type. Differences have been noted in the affinity for gliadin and glutenin of the R5 and the 401/21 antibodies across test kits [ 27 ]. Differences have also been observed between values obtained using R5 sandwich and competitive methods for gluten-containing cereals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A polyclonal antibody against gluten proteins is also available from the Morinaga Institutes of Biological Sciences, Inc., (MIoBS). The Skerritt antibody was raised against wheat gliadin and has been shown to recognize the HMW glutenins (1618). The R5 antibody was raised against rye secalin and strongly binds to the QQPFP, QQQFP, LQPFP, and QLPFP epitopes in α-/β-, ω-, and γ-gliadins (19, 20).…”
Section: Introductionmentioning
confidence: 99%